Advanced glycation endproducts are increased in rheumatoid arthritis patients with controlled disease - de Groot, Lodewijk (BioMed Central, 2011)
INTRODUCTION: Advanced glycation end products (AGEs) are produced and can accumulate during chronic inflammation, as might be present in patients with rheumatoid arthritis (RA). AGEs are involved in the development of cardiovascular disease. The aim of this study is to evaluate whether AGEs are increased in patients with long-standing RA and whether AGE accumulation is related to disease activity, disease severity and measures of (premature) atherosclerosis, such as endothelial activation, endothelial dysfunction and intima media thickness (IMT). METHODS: In a cross-sectional study, 49 consecutive RA patients with longstanding disease (median disease duration of 12.3 years (range 9.3 to 15.1)), receiving standard of care, were included and compared with 49 age- and sex-matched healthy controls (HC). AGEs were determined by skin autofluorescence. Disease activity was evaluated by the Disease Activity Score of 28 joints (DAS-28) score and joint damage by modified Sharp-v.d. Heijde score. Endothelial activation (soluble vascular cellular adhesion molecule-1) sVCAM-1, von Willebrand factor (vWF), thrombomodulin), endothelial dysfunction (determined by small artery elasticity (SAE)) and IMT were measured and related to AGE accumulation. RESULTS: AGEs were increased in RA patients (median 2.4 arbitrary units (a.u.), range 1.6 to 4.2) compared to HC (2.2, 1.3 to 3.8). RA patients had a DAS-28 score of 2.9 (0.8 to 6.9) and a modified Sharp-v.d. Heijde score of 19 (0 to 103). sVCAM-1 and vWF levels were higher in RA patients. SAE was significantly decreased in RA (3.9 ml/mmHg (1.4 to 12.2) vs. 6.1 in HC (1.7 to 12.9). IMT did not differ between the two groups. Combining both groups' AGEs correlated with vWF, sVCAM-1 and IMT, and was inversely related to SAE. In RA, AGEs had an inverse relation with SAE, but did not relate to disease activity or radiological damage. In multivariate analysis for both groups, smoking, glucose levels, vWF, SAE and male gender were significantly related to the formation of AGEs. CONCLUSIONS: AGEs were increased in RA patients with long-standing disease and without signs of premature atherosclerosis. AGEs were related to endothelial activation and endothelial dysfunction. This supports the hypothesis that in RA AGEs may be an early marker of cardiovascular disease.